2022
DOI: 10.1155/2022/9355206
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Amniotic Membrane Transplantation on Trabeculectomy in Patients with Pseudoexfoliation Glaucoma

Abstract: Purpose. The aim is to evaluate the effect of amniotic membrane transplantation (AMT) on trabeculectomy with mitomycin C in patients with pseudoexfoliation glaucoma (PXG). Methods. This retrospective cohort study included 85 eyes of PXG who underwent trabeculectomy with or without AMT (52/33 eyes in the AMT/control group). Surgical success was defined by these criteria: (1) intraocular pressure (IOP) ≤18 mmHg and IOP reduction ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Trabeculectomy with amniotic membrane transplantation (AMT) above or under the scleral flap had a high success rate and fewer complications [ 10 12 ]. We previously evaluated the effect of AMT on trabeculectomy and found that it was a safe and effective procedure for intraocular pressure (IOP) reduction in patients with primary open-angle glaucoma (POAG) and pseudoexfoliation glaucoma [ 13 , 14 ]. Furthermore, the incidence of avascular blebs was significantly lower in the AMT group than in the control group.…”
Section: Introductionmentioning
confidence: 99%
“…Trabeculectomy with amniotic membrane transplantation (AMT) above or under the scleral flap had a high success rate and fewer complications [ 10 12 ]. We previously evaluated the effect of AMT on trabeculectomy and found that it was a safe and effective procedure for intraocular pressure (IOP) reduction in patients with primary open-angle glaucoma (POAG) and pseudoexfoliation glaucoma [ 13 , 14 ]. Furthermore, the incidence of avascular blebs was significantly lower in the AMT group than in the control group.…”
Section: Introductionmentioning
confidence: 99%